Fabrication of nanowire using ash trimming technique - Tijjani Adam, Shuwa; Uda, Hashim, Prof. Dr.; Leow, Pei Ling; Qazi Muhammad, Humayun (Trans Tech Publications, 2013)
Link to publisher's homepage at http://www.ttp.net/